The Role of Correctional Institutions in the Development of Prisoners to Prevent Recidivism of Crimes in Sorong City - Rahul Pieter S. Yapen; Wahab Aznul Hidaya; Muharuddin Muharuddin (Faculty of Law, Universitas Muhammadiyah Sorong, 2024)
Abstract : Correctional Institution Class II B Sorong is very functional in fostering recidive inmates where in the system of implementing correctional guidance is very necessary participation or participation of the Community, both by cooperating in fostering and being willing to accept back recidive inmates who have completed serving their sentences. This research is an empirical-normative research that prioritizes the results of interviews. The types of data used by the author are primary data and secondary data. The data collection techniques used are literature and field research in the form of interviews. Data analysis used in this research is descriptive-qualitative analysis, namely describing the juridical review of the coaching of recidive prisoners. The coaching of recidive prisoners at the Class II B Sorong Correctional Institution has 3 stages, namely, the initial stage includes the admission stage, orientation and independence coaching stage, from the coaching stage carried out by the Class II B Sorong Correctional Institution is in accordance with Law Number 12 of 1995 concerning Corrections or renewal of Law Number 22 of 2022 concerning Corrections. It's just that the implementation has not been carried out optimally due to several things, among others: lack of correctional officers in the field of religion, lack of health workers, and no surveillance cameras (CCTV), as well as inadequate facilities and infrastructure at the Class II B Sorong Correctional Institution. To the Correctional Institution Class II B Sorong to add Correctional officers and increase cooperation with agencies that can assist in carrying out the guidance of recidive prisoners so that in the future it will be even better.